2022
DOI: 10.3390/ph15010108
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Tablets: A Valid Strategy to Combine Efficacy and Safety in Pediatrics

Abstract: In the treatment of pediatric diseases, mass-produced dosage forms are often not suitable for children. Commercially available medicines are commonly manipulated and mixed with food by caregivers at home, or extemporaneous medications are routinely compounded in the hospital pharmacies to treat hospitalized children. Despite considerable efforts by regulatory agencies, the pediatric population is still exposed to questionable and potentially harmful practices. When designing medicines for children, the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 55 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, Klingmann et al reported that in children aged 6 months and older, administration of 25 or more mini-tablets was well tolerated, feasible, safe, and superior to equivalent doses of syrup [ 19 ], suggesting the possibility that mini-tablets could be used for oral medications at higher doses. The results of these studies support the transition from syrups to small-solid dosage forms for children of all ages, as advocated by the WHO [ 15 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, Klingmann et al reported that in children aged 6 months and older, administration of 25 or more mini-tablets was well tolerated, feasible, safe, and superior to equivalent doses of syrup [ 19 ], suggesting the possibility that mini-tablets could be used for oral medications at higher doses. The results of these studies support the transition from syrups to small-solid dosage forms for children of all ages, as advocated by the WHO [ 15 ].…”
Section: Discussionsupporting
confidence: 74%
“…Mini-tablets have garnered interest as a novel form of solid medication for children. They employ the same manufacturing techniques, equipment, and formulation as their adult counterparts and are less prone to taste or texture issues [ 15 ]. Klingmann et al compared the acceptability and ability to swallow a syrup formulation and an uncoated mini-tablet (2 mm diameter) in 306 children aged 6 months to 6 years and found that the mini-tablet was superior [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving adequate dosing of medicines in the paediatric population while ensuring safety is challenging [ 1 ], as children are often unable to ingest standard-sized solid dose formulations and find many oral medications unpalatable [ 1 , 2 ]. In addition, a drug’s pharmacokinetic profile may be influenced by age and body weight, highlighting a potential need for flexible dosing for paediatric populations [ 1 ]. There has been a great effort over the past two decades to develop age-appropriate formulations of medicines for paediatric use [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a drug’s pharmacokinetic profile may be influenced by age and body weight, highlighting a potential need for flexible dosing for paediatric populations [ 1 ]. There has been a great effort over the past two decades to develop age-appropriate formulations of medicines for paediatric use [ 1 , 2 , 3 , 4 ]. While conventional formulations, such as syrups, are commonplace in paediatric medicine, these formulations can sometimes have disadvantages, such as drug instability, poor palatability, the uncontrolled release of active compounds, inconsistent dosing due to incomplete swallowing, and limited knowledge of which excipients are safe for use in the paediatric population [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation